Opportunities and challenges for improving a Colombian public research program in plant breeding and plant genetic resources lead by Agrosavia - Galeano, Carlos H.; Tehelen, Katherine; Jiménez, Hugo R.; González, Carolina; Cerón Souza, Ivania (Publicador no identificado, 2024)
Agrosavia (Corporación Colombiana de Investigación Agropecuaria) is the Colombian state institution in charge of the agricultural research at the national level, including plant breeding. Since 2014, Agrosavia started to increase its research staff and has reset the leadership of public research to solve the needs of the agricultural sector population, focusing on small producers. However, the current team working on plant breeding and plant genetic resources are facing some challenges associated with generation gaps and the lack of a collaborative working plan for the next years. To identify the opportunities and actions in this research area, we surveyed all the 52 researchers working in Agrosavia in this area in 2017. We analyzed the opinions of researchers to detect the strengths and weaknesses of the program using a sentiment score. We also examined the networking to test both how consolidated the group is and if among top leaders are gender parity and also have a higher academic degree. Results showed that there is a mixed community of old and new researchers with clear gender bias in the proportion of male-female. Within the network, the interactions are weak, with several subgroups where the top-ten of both central leaders and the most influencer are frequently males with mostly an M.Sc. degree but with significant experience in the area. Researchers have an interest in 31 crops. From them, 26 are in the national germplasm bank, but this bank is not the primary source for their breeding programs. The top-five of plants with increasing interest are corn, cocoa tree, golden berries, oil palm, and sugarcane. Researchers also want to establish collaborations with 54 different institutions, where the Universidad Nacional de Colombia, which is the top public university in the country, is on the head. Researchers also perceived weaknesses in the marker-assisted selection, experimental design, and participatory plant breeding, but those criticisms have a positive sentiment score average of 1.55 (0.3 SE) across 31 texts analyzed. Based on all results, we identified five critical strategic principles to improve the plant-breeding research program. They include a gender diversity policy to hire new researchers strategically to reduce the gender gap and strength the generational shift. Better collaboration between the national germplasm bank and plant breeding research. A coordinate plan where the studies focus on food security crops that the government supports independently of market trends. And finally, adequate spaces for the project’s design and training programs. Hence, we recommend the creation of a consultant group to implement these policies progressively in the next years.